Perioperative nutritional interventions for gastric cancer patients: a meta-analysis of surgical outcomes - Li, QiJun; Chen, Chen; Wang, XiaoHong (Frontiers in Nutrition, 2025)
ObjectiveTo assess the effectiveness of nutritional interventions such as multimodal nutrition interventions, dietary education and digital interventions, immunonutrition, and oral nutritional supplements (ONS) on clinical, immunological, and biochemical outcomes among gastric cancer patients.BackgroundNutritional interventions become a key element in enhancing clinical, immunological, and biochemical outcomes in those who have gastric cancer and are receiving surgery, chemotherapy, or follow-up care after discharge.MethodsEighteen randomized controlled trials (RCTs) were included, examining interventions like multimodal nutrition (EN, PN, probiotics, early oral feeding), dietary counseling, digital platforms, immunonutrition (ω-3, arginine, RNA-enriched formulas), and ONS. Primary outcomes were albumin (Nutritional marker used to assess malnutrition), CRP(C-reactive protein biomarker for systemic inflammation), IgA, interleukins, weight, quality of life, complications, and mortality. Data were pooled with a random-effects model with inverse variance methods to estimate standardized mean differences (SMD) with 95% confidence intervals (CI). Heterogeneity was measured using the I2 statistic.ResultsSeparate studies indicated the following benefits with respective interventions: improvement in albumin, CRP, immunological markers, weight, quality of life, and fewer complications. Pooled analyses, however, revealed no statistically significant effects overall: multimodal nutrition (SMD −0.43, 95% CI −0.99 to 0.13), dietary counseling/education/digital interventions (SMD 0.27, 95% CI −0.34 to 0.88), immunonutrition (SMD −0.16, 95% CI −0.58 to 0.26), and ONS (SMD 0.07, 95% CI −0.27 to 0.41). Strong heterogeneity was identified for all interventions (I2 range: 85–88%, p < 0.01), indicating variability in study populations, intervention types, durations, and outcomes measured.ConclusionAlthough single trials indicate nutritional interventions can enhance biochemical, immunological, and clinical responses in gastric cancer patients, pooled evidence fails to show overall consistent benefits. Substantial heterogeneity emphasizes the need for larger, uniform trials to establish proper nutritional interventions, formulations, and timing. These findings validate the potential usefulness of individually tailored nutritional support as an adjunct to conventional treatment.